High resting metabolic rate among Amazonian forager‐horticulturalists experiencing high pathogen burden. Issue 3 (4th July 2016) - Gurven, Michael D.; Trumble, Benjamin C.; Stieglitz, Jonathan; Yetish, Gandhi; Cummings, Daniel; Blackwell, Aaron D.; Beheim, Bret; Kaplan, Hillard S.; Pontzer, Herman
Abstract: Objectives: Resting metabolic rate (RMR) reflects energetic costs of homeostasis and accounts for 60 to 75% of total energy expenditure (TEE). Lean mass and physical activity account for much RMR variability, but the impact of prolonged immune activation from infection on human RMR is unclear in naturalistic settings. We evaluate the effects of infection on mass‐corrected RMR among Bolivian forager‐horticulturalists, and assess whether RMR declines more slowly with age than in hygienic sedentary populations, as might be expected if older adults experience high pathogen burden. Materials and Methods: RMR was measured by indirect calorimetry (Fitmate MED, Cosmed) in 1, 300 adults aged 20 to 90 and TEE was measured using doubly labeled water ( n = 40). Immune biomarkers, clinical diagnoses, and anthropometrics were collected by the Tsimane Health and Life History Project. Results: Tsimane have higher RMR and TEE than people in sedentary industrialized populations. Tsimane RMR is 18 to 47% (women) and 22 to 40% (men) higher than expected using six standard prediction equations. Tsimane mass‐corrected TEE is similarly elevated compared to Westerners. Elevated leukocytes and helminths are associated with excess RMR in multivariate regressions, and jointly result in a predicted excess RMR of 10 to 15%. After age 40, RMR declines by 69 kcal/decade ( p < .0001). Controlling for lean mass and height accounts for 71% of age‐related RMR decline, and adding indicators of infection minimally affects the age slope. The residual level of age‐related decline from age 40 is 1.2% per decade. Conclusion: High pathogen burden may lead to higher metabolic costs, which may be offset by smaller body mass or other energy‐sparing mechanisms.